Evolutionary origin of the type 2 corticotropin‐releasing hormone receptor γ splice variant. (3rd March 2019) - De Groef, Bert; Wawrzyczek, Stanisław K.; Watanabe, Yugo; Noy, Ellyse B.; Reser, David H.; Grommen, Sylvia V. H.
Abstract: Many G protein‐coupled receptors have splice variants, with potentially different pharmaceutical properties, expression patterns and roles. The human brain expresses three functional splice variants of the type 2 corticotropin‐releasing hormone: CRHR2α, –β and –γ. CRHR2γ has only been reported in humans, but its phylogenetic distribution, and how and when during mammalian evolution it arose, is unknown. Based on genomic sequence analyses, we predict that a functional CRHR2γ is present in all Old World monkeys and apes, and is unique to these species. CRHR2γ arose by exaptation of an intronic sequence—already present in the common ancestor of primates and rodents—after retrotransposition of a short interspersed nuclear element (SINE) and mutations that created a 5′ donor splice site and in‐frame start codon, 32–43 million years ago. The SINE is not part of the coding sequence, only of the 5′ untranslated region and may therefore play a role in translational regulation. Putative regulatory elements and an alternative transcriptional start site were added earlier to this genomic locus by a DNA transposon. The evolutionary history of CRHR2γ confirms some of the earlier reported principles behind the "birth" of alternative exons. The functional significance of CRHR2γ, particularly in the brain, remains to be showed. Abstract : Based on genomic sequence analyses, we predict that a functional CRHR2g is present in all Old World monkeys and apes, and is unique to these species. CRHR2g arose by exaptation of an intronic sequence—already present in the common ancestor of primates and rodents—after retrotransposition of a short interspersed nuclear element (SINE) and mutations that created a 5′ donor splice site and in‐frame start codon, 32–43 million years ago.